Robotic assisted laryngopharyngoesophagectomy in an advanced carcinoma of hypopharynx- assistance of newer surgical armamentarium in an advanced malignancy - N. Parvataneni; Deepthi Kancharla; Kiran Kumar D; Ishfaq Ahmad Gilkar; P. Susmitha; Mahesh Chejarla (Elsevier, 2023)
Still in today's advanced era to reconstruct surgical abnormalities following removal of upper airway and proximal esophageal malignancies is regarded a herculean task which does require tremendous surgical experience and expertise and multidisciplinary team work. In this short communication we are presenting a case of advanced carcinoma hypopharynx which was surgically managed with laryngopharyngoesophagectomy with Robotic assistance.